Lorenzo de' Medici and the art of magnificence - Kent, F. W. (Francis William), 1942- (Baltimore : Johns Hopkins University Press, 2004)
"In the past half century, scholars have downplayed the significance of Lorenzo de' Medici (1449-1492) as a patron of the arts. Less wealthy than his grandfather Cosimo, the argument goes, Lorenzo was far more interested in collecting ancient objects of art than in commissioning contemporary art or architecture. His earlier reputation as a patron was said to be largely a construct of humanist exaggeration and partisan deference."
"Historian F.W. Kent offers a new look at Lorenzo's relationship to the arts, aesthetics, collecting, and building - especially in the context of his role as the political boss (maestro della bottega) of republican Florence and a leading player in Renaissance Italian diplomacy. Kent's approach reveals Lorenzo's activities as an art patron as far more extensive and creative than previously thought. Known as "the Magnificent," Lorenzo was broadly interested in the arts and supported efforts to beautify Florence and the many Medici lands and palaces. His expertise was well regarded by guildsmen and artists, who often turned to him for advice as well as for patronage
Lorenzo was educated in the arts by such men, and Kent explores his aesthetic education and taste, taking into account what is known of Lorenzo's patronage of music and manuscripts, and of his own creative works as a major Quattrocento poet." "Illustrated with photographs of Medici landmarks by Ralph Lieberman, Lorenzo de' Medici and the Art of Magnificence offers a portrait of Lorenzo as a man whose achievements might have rivaled his grandfather's had he not died so young."--Jacket
Introduction : the myth of Lorenzo -- The aesthetic education of Lorenzo -- The temptation to be magnificent, 1468-1484 -- Lorenzo and the Florentine building boom, 1485-1492 -- Lorenzo, "Fine husbandman," and Villa-Builder, 1483-1492.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Medici, Lorenzo de', -- 1449-1492.; Medici, Lorenzo de', -- 1449-1492.; Medici, Lorenzo de', -- 1449-1492.; Medici, Lorenzo de', -- 1449-1492; Medici, Lorenzo de'; Statesmen -- Italy -- Florence -- Biography; Intellectuals -- Italy -- Florence -- Biography; Florence (Italy) -- History -- 1421-1737.; Hommes d'État -- Italie -- Florence -- Biographies; Intellectuels -- Italie -- Florence -- Biographies; Florence (Italie) -- Histoire -- 1421-1737.; ART -- Individual Artists -- Monographs; BIOGRAPHY & AUTOBIOGRAPHY -- Artists, Architects, Photographers; ART -- Individual Artists -- Artists' Books; ART -- Individual Artists -- Essays; Intellectuals; Statesmen; Italy -- Florence; Kunst; Repräsentation; Kunstbevordering; Beeldende kunsten; 1421-1737; collective biographies; Biographies; History; Biographies; Biographies